The prevalence, risk factors, and complications of Clostridium difficile infection in a tertiary care center, western region, Saudi Arabia. Issue 10 (October 2022) - Althaqafi, Abdulhakeem; Munshi, Adeeb; Baghlaf, Bayan; Munshi, Enas; Malakah, Manar; Almarhabi, Hassan; Alharbi, Maher; Alsaedi, Asim
Abstract: Background: Clostridium difficile is an anaerobic gram-positive spore-forming bacillus that is most commonly associated with nosocomial diarrhea. This study aimed to analyze the prevalence and risk factors of Clostridium difficile infection (CDI) at a tertiary health care center, Western region, Saudi Arabia. We also aimed to examine the duration of exposure to each risk factor prior CDI development, and to categorize CDI as severe and non-severe depending on the white blood cell (WBC) count. Various complications of the infection were also analyzed. Methods: We performed a retrospective chart review of all patients who had a positive nucleic acid amplification test (NAAT) for Clostridium difficile toxin genes between October 2018 and October 2020. Results: The prevalence of CDI among the included patients was 9.1% (237 of 2611 patients). The mean age (standard deviation) was 56.86 (21) years, and the infection was more prevalent among men (52.74%) than among women (47.26%). The most common risk factor associated with CDI was recent antibiotic use (74.68%), followed by recent acid suppressant use (67.50%), malignancy (46%), and previous gastrointestinal surgery (6.30%). The CDI recurrence rate was 13.90%. Piperacillin-tazobactam was the most frequently used broad-spectrum antibiotic, and was used in 38.8% of the patients, followed by meropenem. The most common malignancy type was lymphoma (22.94%, n = 25), followed by leukemia (n = 23). The most common type of surgery was subtotal colectomy (n = 6). Three patients underwent transverse colon resection, and two underwent ileocecal resection. Hypotension was the most frequently recorded complication (28.40%) in the study population. Conclusion: The prevalence rate of CDI among the study patients during the two-year study from October 2018 to October 2020 was 9.1%. Appropriate use of antibiotic and acid suppressants, and contact isolation measures can help in decreasing the number of CDI cases.